ENHANCEMENT OF NODE ENERGY LIFETIME & BATTERY CONSUMPTION IN WIRELESS SENSOR NETWORK - Kanika Nagpal, Kuldeep Sharma (International Journal of Research Science and Management, 2016)
In this research paper to study the difference between the WSN and Ad-Hoc networks were also covered. It is important to realize that the two networks occupy different areas and applications, but that there is minimal overlap. In this protocol there is a comparison between conventional approach and our approach. This paper presents here “Enhancement of Node Energy lifetime & Battery Consumption in wireless sensor network” through the routing protocol. In this thesis we have concentrated on less consuming energy issue & save battery consumption or to develop a larger the lifetime of system in data transmission. The proposed approach enables a high rate of successful delivery of messages and it results in short route lengths to recover from packet losses.at the two networks occupy different areas and applications, but that there is minimal overlap.